2015
DOI: 10.3389/fpsyg.2015.01368
|View full text |Cite
|
Sign up to set email alerts
|

Changes in aspects of social functioning depend upon prior changes in neurodisability in people with acquired brain injury undergoing post-acute neurorehabilitation

Abstract: Post-acute community-based rehabilitation is effective in reducing disability. However, while social participation and quality of life are valued as distal outcomes of neurorehabilitation, it is often not possible to observe improvements on these outcomes within the limited time-frames used in most investigations of rehabilitation. The aim of the current study was to examine differences in the sequence of attainments for people with acquired brain injury (ABI) undergoing longer term post-acute neurorehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The MPAI-4 has well-documented psychometric properties. Previous studies have described good internal consistency, construct and concurrent validity, as well as predictive validity (15, 8183). In addition, the MPAI-4 was found to be sensitive to clinical change following rehabilitation (84, 85).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…The MPAI-4 has well-documented psychometric properties. Previous studies have described good internal consistency, construct and concurrent validity, as well as predictive validity (15, 8183). In addition, the MPAI-4 was found to be sensitive to clinical change following rehabilitation (84, 85).…”
Section: Methodsmentioning
confidence: 89%
“…There is evidence that home and community-based rehabilitation after ABI is effective in reducing disability (1214), and that longer-term rehabilitation programs lead to improved global outcomes such as social participation and quality of life (QoL) (15). In addition, there is evidence supporting the use of occupation-based interventions to improve daily activity performance (16).…”
Section: Introductionmentioning
confidence: 99%
“…Reliability for this measure has been established in caregivers of persons with TBI. [55][56][57][58][59] Data capture-PROs were completed through Assessment Center (https:// www.assessmentcenter.net), either at a designated computer at the site, or on a personal or publically available computer with an internet connection. Study participants typically completed the survey within a 2-week time frame.…”
Section: Tbi-careqol Item Poolsmentioning
confidence: 99%
“…The CIQ comprises 15 items assessing effective role performance in three domains: Home integration (active participation in the operation of the home or household), Social integration (participation in social activities outside the home) and Productivity (regular performance of work, school or volunteer activities). Internal consistency in previous studies has been reported as good, with Cronbach's alpha's ranging from 0.76–0.84 for total scale scores [ 41 , 52 ]. The CIQ is predominately linked to the major life areas (35%), community, social and civic life (31%) and domestic life (19%) chapters of the WHO ICF [ 53 ].…”
Section: Methodsmentioning
confidence: 99%